Nanoparticle anisotropy induces sphere-to-cylinder phase transition in block copolymer melts. Issue 19 (6th May 2022) - Diaz, Javier; Pinna, Marco; Zvelindovsky, Andrei; Pagonabarraga, Ignacio
Abstract : Anisotropic nanoparticles are shown to induce a sphere-to-cylinder phase transition in sphere-forming block copolymer melts, at a modest concentration. The transition is due to the local breaking of symmetry near the particle surface. Abstract : Block copolymer nanocomposites including anisotropic nanoparticles have been previously found to co-assemble into complex structures with nanoparticle alignment. Anisotropic nanoparticles with large aspect ratios are found to modify the morphology of block copolymers at modest concentrations, inducing a sphere-to-cylinder phase transition by breaking the local symmetry in the vicinity of a solid particle. This transition takes place over a wide range of NP lengths comparable with the BCP spacing. Controlling the orientation of uniaxial nanoparticles provides additional control over the global orientation of the block copolymer, as previously reported by experiments.